DIESEL PARTICULATE EMISSIONS EVALUATION FOR SINGLE CYLINDER ENGINE FUELLED WITH ETHANOL AND GAS-OIL SOLUTIONS (Journal of Engineering, 2011)
Particulate matter (PM) emitted from diesel engine exhaust have been measured in terms of mass, using99.98 % pure ethanol blended directly, without additives, with conventional diesel fuel (gas – oil),toget 10 % , 15 %, 20 % ethanol emulsions . The resulting PM collected has been compared with thosefrom straight diesel. The engine used is a stationary single cylinder, variable compression ratio RicardoE6/US. This engine is fully instrumented and could run as a compression or spark ignition.Observations showed that particulate matter (PM) emissions decrease with increasing oxygenatecontent in the fuel, with some increase of fuel consumption, which is due to the lower heating value ofethanol. The reduction in PM formation increased with load increase, maximum reduction were 58% at1800 rpm. There was no significant reduction observed at low loads. It could be concluded from thetest results that ethanol may be an alternative to / or partially substitute, fossil fuels.